2010
DOI: 10.1016/j.ntt.2009.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral teratogenicity of perfluorinated alkyls in an avian model

Abstract: Link to publication in University of Groningen/UMCG research database Citation for published version (APA): Pinkas, A., Slotkin, T. A., Brick-Turin, Y., Van der Zee, E. A., & Yanai, J. (2010). Neurobehavioral teratogenicity of perfluorinated alkyls in an avian model. Neurotoxicology and Teratology, 32(2), 182-186. https://doi.org/10.1016/j.ntt.2009.11.004 Copyright Other than for strictly personal use, it is not permitted to download or to forward/distribute the text or part of it without the consent of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Effects were most pronounced for individuals exposed during development (Johansson et al, 2009(Johansson et al, , 2008. At the molecular level, correlations have been found between exposure to PFOS or PFOA and changes in the cholinergic system in rodents (Johansson et al, 2008) and protein kinase C (involved in neurotransmission by G protein-coupled receptors) in hatchlings (Pinkas et al, 2010). Taken together, these findings suggest that PFASs may disrupt the function of the nervous system.…”
mentioning
confidence: 84%
“…Effects were most pronounced for individuals exposed during development (Johansson et al, 2009(Johansson et al, , 2008. At the molecular level, correlations have been found between exposure to PFOS or PFOA and changes in the cholinergic system in rodents (Johansson et al, 2008) and protein kinase C (involved in neurotransmission by G protein-coupled receptors) in hatchlings (Pinkas et al, 2010). Taken together, these findings suggest that PFASs may disrupt the function of the nervous system.…”
mentioning
confidence: 84%
“…The PFOS induced apoptosis was connected to activation of different subtypes of protein kinase C (PKC-α, PKC-βII and PKC-ε). The effect of PFOS and PFOA on PKC-translocation was also observed by Pinkas et al ( 2010 ) on developmentally exposed chicks as described in the previous section. PKC is involved in a range of processes in the brain such as cognitive functions, learning and memory and several of studies have shown that other environmental toxicants, such as PCBs, dioxins and brominated fl ame retardants also infl uence PKC activity (Kodavanti et al 1994 ).…”
Section: Cell Cultures ( In Vitro Studies)mentioning
confidence: 73%
“…Different PKC isoforms have previously been postulated as possible targets following both adult and developmental exposure to halogenated aromatic hydrocarbons, such as the PCBs (Kodavanti et al 1994(Kodavanti et al , 1998Yang et al 2003 ). The doses used in the experiment by Pinkas et al ( 2010 ) lead, however to high mortality. Between 30 and 50 % of the exposed eggs did not develop embryos indicating that the doses used were detrimental to the chicks leading to other substantial non-neurotoxic effects.…”
Section: Chickenmentioning
confidence: 97%
See 1 more Smart Citation
“…Neonatal exposure of mice to PFOA (and PFOS) affected the proteins involved in neurogenesis and synaptogenesis in the developing mouse brain, which were accompanied by neurobehavioral defects in adulthood (Johansson et al, 2008). Also in an avian model PFOA was reported to be a developmental neurotoxicant (Pinkas et al, 2010). In summary, PFOA exposures in rodent indicate carcinogenic responses in liver, pancreas, testes and mammary glands.…”
Section:  Neurotoxicitymentioning
confidence: 95%